Defining the nonreturn time for intestinal ischemia reperfusion injury in mice - Stringa, Pablo Luis (2012)
Among the abdominal organs, the intestine is probably the most sensitive to ischemia reperfusion injury (IRI), a phenomenon that occurs in many intestinal disorders. Few studies have reported in detail the impact of intestinal ischemia time in mice. We evaluated the effect of various warm intestinal ischemia times in an intestinal IRI model in mice. Adult male Balb/c mice were divided into 4 groups that differed in intestinal ischemia time: G1, 30; minutes; G2, 35 minutes; G3, 40 minutes; and G4, 45 minutes. Histological evaluation showed average Park scores as follows: G1 0.6 ± 0.55; G2 1.8 ± 0.45; G3 4.8 ± 2.25; and G4 5 ± 1.79. All animals from G1 survived 30 hours. G2 animals showed intermediate behavior with all succumbing between 18 and 30 hours postprocedure. G3 and G4 displayed similar survival results with animals succumbing before 6 hours after intestinal reperfusion. These data showed that Park index scores of 3 or higher were related to early death. We concluded that the 5 minutes between 35 and 40 minutes is the critical limit, after which all mice die after reperfusion. This result may represent a valuable tool for future research in mice.